Clinical evaluation of different therapeutic modalities in psoriasis by Pasi score - Neerja Puri; Bharat Bhushan Mahajan; Samarjeet Kaur Sandhu (Our Dermatology Online, 2013)
Psoriasis is a chronic recurrent papulosquamous disorder characterized by epidermal hyperplasia. The management of psoriasis can be challenging. Although, there are many therapeutic modalities available but still there are no clear cut guidelines regarding the usage of different modalities depending on the severity of psoriasis evaluated by PASI score. Taking this into consideration, a randomized controlled trial was undertaken to clinically evaluate different therapeutic modalities in psoriasis by PASI scoring. We selected fifty clinically diagnosed cases of psoriasis and confirmed by histopathology. The patients were put on different modalities depending on the psoriasis area and severity index score (PASI score) and all the patients were followed up to 24 weeks for any relapse.